Perancangan Area Kerja Lantai Produksi Berdasarkan Metode 5s (Seiri, Seiton, Seiso, Seiketsu, Shitsuke) - Isana Arum Primasari; Arjun Hidayanto (LPPM Universitas Putera Batam, 2022)
The Official Seminar Kit Package is one of the SMEs supporting the economy in Indonesia which is engaged in the business of producing bags, documents, and books as a seminar facility. Initial observations in the production area found an irregular production room because all the equipment used for work was on the workbench This causes workers to find it difficult when looking for one of the equipment to be used because it is not fixed in its placement, sometimes the equipment is lost because it falls from the work table so workers need time to find the equipment. Another incident is that there are items that are not used but are still in the workspace and mixed with equipment that is being used so that this adds to the chaos of the workspace. The remaining production materials are also mixed with raw materials that are still used, resulting in workers having to first sort out the raw materials to be used. After the job is done, workers just collect all the equipment and put it in one tool case without sorting it out. Evaluation of the implementation of 5 S (Seiri, Seiton, Seiso, Seiketsu and Shitsuke) needs to be done to make improvements to the layout of the work area by auditing each work station. The score results from the implementation of 5S are the basis for setting the layout in the production area. The purpose of applying the 5S method is to organize and maintain the work area to create a clean, neat and orderly work atmosphere, so as to increase work productivity.. The results obtained from the implementation of 5S are when the initial conditions are still classified as poor criteria with an application value of 27% at cutting work stations, checking and providing accessories work stations, and packaging work stations, and the application value is 29% at work stations. screen printing and sewing workstations. After improving the layout of the work area, an increase in the results of applying 5S was obtained by 76% at the cutting work station and screen printing work station, 78% at the sewing work station, and the application value of 80% at the checking work station and providing accessories as well. packaging work station. Based on the results of this study, it can be concluded that the improvement of the work area using the 5S method has been able to increase the percentage of success in implementing 5R in the work area